Metagenomic characterization reveals virus coinfections associated with Newcastle disease virus among poultry in Kenya - Panyako, P.M.; Ommeh, S.C.; Kuria, S.N.; Lichoti, J.K.; Musina, J.; Nair, V.; Nene, Vishvanath M.; Oyola, Samuel O.; Munir, M. (Wiley, 2023)
Newcastle disease (ND) is an endemic viral disease affecting poultry and causing massive economic losses. This cross-sectional purposive study detected coinfections that are associated with the Newcastle disease virus among poultry from selected regions in Kenya. Cloacal (n = 599) and oral–pharyngeal (n = 435) swab samples were collected and pooled into 17 and 15 samples, respectively. A total of 17,034,948 and 7,751,974 paired-end reads with an average of 200 nucleotides were generated from the cloacal and oral–pharyngeal swab samples, respectively. Analysis of the de novo assembled contigs identified 177 and 18 cloacal and oral–pharyngeal contigs, respectively with hits to viral sequences, as determined by BLASTx and BLASTn analyses. Several known and unknown representatives of Coronaviridae, Picobirnaviridae, Reoviridae, Retroviridae, and unclassified Deltavirus were identified in the cloacal swab samples. However, no Newcastle disease virus (family Paramyxoviridae) was detected in the cloacal swabs, although they were detected in the oropharyngeal swabs of chickens sampled in Nairobi, Busia, and Trans Nzoia. Additionally, sequences representative of Paramyxoviridae, Coronaviridae, and Retroviridae were identified in the oral–pharyngeal swab samples. Infectious bronchitis virus and rotavirus were chickens' most prevalent coinfections associated with the Newcastle disease virus. The detection of these coinfections suggests that these viruses are significant threats to the control of Newcastle disease as the Newcastle disease virus vaccines are known to fail because of these coinfections. Therefore, this study provides important information that will help improve disease diagnosis and vaccine development for coinfections associated with the Newcastle disease virus.